Chitosan-based coacervate polymers for propolis encapsulation: Release and cytotoxicity studies - Sato, Tabata [UNESP]; Mello, Daphne [UNESP]; Vasconcelos, Luana [UNESP]; Valente, Artur; Borges, Alexandre [UNESP] (MDPI, 2020)
Chitosan-DNA (CS-DNA) and Chitosan-Pectin (CS-P) hydrogels were formulated as a sustained drug delivery carrier for drug delivery. For this, hydrogels were prepared by emulsion technique: mixing aqueous phase of the CS and DNA or P solution with benzyl alcohol using a high-performance dispersing instrument. Green Propolis (GP) was incorporated by imbibition: hydrogels were placed in GP aqueous solution (70 µg/mL) for 2 h. The specimens were freeze-dried and then characterized using different techniques. In vitro cell viability and morphology were also performed using the MG63 cell line. The presence of P was evidenced by the occurrence of a strong band at 1745 cm-1, also occurring in the blend. DNA and CS-DNA showed a strong band at 1650 cm−1, slightly shifted from the chitosan band. The sorption of GP induced a significant modification of the gel surface morphology and some phase separation occurs between chitosan and DNA. Drug release kinetics in water and in saliva follow a two-step mechanism. Significant biocompatibility revealed that these hydrogels were non-toxic and provided acceptable support for cell survival. Thus, the hydrogel complexation of chitosan with DNA and with Pectin provides favorable micro-environment for cell growth and is a viable alternative drug delivery system for Green Propolis.
Keywords: Chitosan; DNA; Hydrogel; Pectin; Propolis